Implementation of Physical Education In Inclusion Schools: A Systematic Literature Review - Indra Wijayanto; Dwi Gansar Santi Wijayanti (Journal of Physical Education Health and Sport, 2025)
Background: This study discusses how physical education is taught in inclusive schools in the context of physical education teachers, inclusive/disabled students, and its application in inclusive schools. Research Objective: The objective of this study is to examine the implementation of physical education in inclusive schools based on findings from various literature. Methodology: The PRISMA standards were used for a systematic review and meta-analysis covering the period from 2020 to 2025. The keywords “Implement”, “Physical”, “Inclusive”, and “School” were used in the search procedure. The search engine utilized a total of 348 articles were obtained from Scopus databases. After applying the Inclusion criteria, only 8 articles remained. Findings/Results: Various studies highlight the role of physical education teachers and understanding the factors influencing students with disabilities as key factors for success and effectiveness in promoting inclusive physical education implementation. Conclusion: The role of physical education teachers in inclusive schools is a frequently discussed topic in this review. Some limitations inherent in this review should be noted. For future research, it would be interesting to add new keywords or topics related to coaches and athletes.